La Commission exprime son point de vue sur l'échec de Cancun - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Le Commissaire au commerce Pascal Lamy s'est adressé au...